Utrata legitymizacji prawa według koncepcji Ronalda Dworkina - Jabłoński, Paweł (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The aim of the paper is to analyse the answer that Dworkin’s philosophy of law provides to the following question: what is the threshold of wickedness of the legal order that excuses citizens from the moral obligation to obey the law? This is not a problem of civil disobedience (which only contests a particular decision of making or applying the law), but a situation in which the whole political-legal system is the object of moral contestation. The task will be carried out in three steps. In the first one, I will outline Dworkin’s theory of political obligation, situating it in the broader framework of the debate on this obligation. In the second step, I will analyse one of the main elements of this theory, namely the legitimacy of the legal order. As a third step, I will draw attention to a rather — as it seems — surprising similarity between Dworkin’s argumentation and Radbruch’s formula.
Keywords: Dworkin, Ronald (1931-2013); zobowiązanie polityczne; szacunek dla prawa; równa troska i poszanowanie